The Impact of Prenatal Environmental Tobacco Smoking (ETS) and Exposure on Chinese Children: A Systematic Review - Huazhen Ye; Xiaoyu Yang; Fahad Hanna (MDPI AG, 2023)
Background: There is considerable evidence to support the association between exposure to environmental tobacco smoke (ETS) and children's burden of disease. However, the literature on the health outcomes of prenatal ETS exposure among Chinese children has not yet been comprehensively reviewed. Objective: This systematic review examines the currently available evidence and identifies gaps for further research on the health consequences of prenatal ETS exposure on Chinese children. Methods: Following the JBI systematic-scoping review methodological framework, we conducted a computer-aided search of three electronic databases-PubMed, EBSCOhost, and ProQuest to include studies from January 2011 to May 2023 that addressed the health outcomes of Chinese children whose mothers were exposed to ETS at any stage of pregnancy. Furthermore, a methodological quality assessment of the selected articles was conducted using JBI critical appraisal checklists. Results: A total of 30 articles were reviewed, including eleven high-quality studies and nineteen moderate-quality studies. Five main themes, including hypertension, fetal and children's development, behavioural disorders, respiratory outcomes, and "other health outcomes", were encompassed. The majority of the studies showed a positive link between prenatal ETS exposure and an increased risk of preterm birth, and moderate risk of fetal growth restriction. A few studies explored other potential adverse outcomes of ETS, including hypertension, respiratory morbidity, lung function, and asthma in children. Conclusions: The currently available evidence on prenatal ETS exposure in Chinese children has unveiled a wide range of health outcomes, including preterm birth, fetal development, behavioural disorders, and much more. However, Chinese studies in this area are still lacking and a gap still exists in relation to the strength of association between prenatal ETS exposure and some health risks. Efficient anti-smoking policies and smoking cessation programs should be developed to promote maternal and child health. Further research is also needed to provide better evidence in this field.